2016
DOI: 10.14692/jfi.12.2.46
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pseudomonas fluorescens Formulation to Control Bacterial Wilt Disease and to Increase Growth of Patchouli Plant

Abstract: Penyakit layu bakteri (Ralstonia solanacearum) merupakan salah satu kendala produksi nilam. Pseudomonas fluorescens Pf19 dapat menginduksi ketahanan nilam terhadap R. solanacearum. Penelitian ini bertujuan untuk mendapatkan dosis dan waktu aplikasi formula P. fluorescens Pf19 optimal yang efektif dan efisien mengendalikan R. solanacearum dan meningkatkan pertumbuhan dan produksi nilam. Hasil pengujian efektivitas dosis (75 dan 100 g L-1) dan waktu aplikasi (setiap 30, 60, 90, dan 120 hari) menunjukkan bahwa fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In Indonesia, less work has been done on genetic diversity of R. solanacearum strains. Most of R.solanacearum studies have been focusing on bacterial wilt disease control, either by application of antagonistic bacteria (Nasrun and Nurmansyah 2016;Saputra et al 2015;Yanti et al 2017) or developing new resistant varieties of plants (Adriani et al 2012;Hartati et al 2015). Most of them involved only one R. solanacearum strain in each study.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, less work has been done on genetic diversity of R. solanacearum strains. Most of R.solanacearum studies have been focusing on bacterial wilt disease control, either by application of antagonistic bacteria (Nasrun and Nurmansyah 2016;Saputra et al 2015;Yanti et al 2017) or developing new resistant varieties of plants (Adriani et al 2012;Hartati et al 2015). Most of them involved only one R. solanacearum strain in each study.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that P fluorescence had a potential to suppress the development of VSD disease and to produce secondary metabolites as high growth regulators, which enhance the growth of cocoa plants. According to Nasrun and Nurmansyah (2016), the formula with the active ingredient of P. fluorescens Pf19 can induce the resistance of patchouli against Ralstonia Solanacearum which causes bacterial wilt disease, and increased patchouli plant growth. Hariprasad et al (2013) showed that a tomato-rhizosphere-associated Pseudomonas sp.…”
Section: Growth Of Shoot (The Number Of Shoots)mentioning
confidence: 99%